2019
DOI: 10.5603/gp.2019.0099
|View full text |Cite
|
Sign up to set email alerts
|

The role of nesfatin and selected molecular factors in various types of endometrial cancer

Abstract: Objectives: Endometrial cancers (ECs) are the most common gynaecological cancers in well developed countries. Diabetes and metabolic syndrome are among the biggest risk factors. Nesfatin-1, the adipokine derivative of NUCB2 (nucleobindin derivative 2) is linked to the clinical course of EC. Molecular factors, including mutations in MLH1 and MHS2 genes, c-MET and ARID1A are also related to prognosis in endometrial cancer. Material and methods:Using sections of paraffin-embedded preparations and immunohistochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Interestingly, there are two types of EC that differ in terms of etiology, biology, and clinical course, i.e., type I EC (endometrioid adenocarcinoma) and type II EC (non-endometrioid adenocarcinoma). The study results demonstrated that in type I EC, nesfatin-1 expression was significantly higher in G1 than G2 and G3 (in total; G1—68.97% compared to G2 and G3—50.4%, p = 0.0487) [ 51 ]. To conclude, the presented results suggest that the expression of NUCB2/NESF-1 may be significant for the prognosis in EC patients.…”
Section: Nucb2—a Predictive/prognostic Biomarker In Cancers?mentioning
confidence: 99%
“…Interestingly, there are two types of EC that differ in terms of etiology, biology, and clinical course, i.e., type I EC (endometrioid adenocarcinoma) and type II EC (non-endometrioid adenocarcinoma). The study results demonstrated that in type I EC, nesfatin-1 expression was significantly higher in G1 than G2 and G3 (in total; G1—68.97% compared to G2 and G3—50.4%, p = 0.0487) [ 51 ]. To conclude, the presented results suggest that the expression of NUCB2/NESF-1 may be significant for the prognosis in EC patients.…”
Section: Nucb2—a Predictive/prognostic Biomarker In Cancers?mentioning
confidence: 99%
“…Currently, it is known that NUCB2 positively correlates with the Gleason grade in prostate cancer and the Fuhrman grade in renal cancer [ 18 , 38 ]. Interestingly, Markowska et al demonstrated that in type I endometrial cancer, the expression of nesfatin-1 was significantly higher in G1 than in G2 and G3 in total ( p < 0.05) [ 39 ]. Our study is the first research that shows the association of NUCB2 with the histological grade in BC.…”
Section: Discussionmentioning
confidence: 99%
“…The polymorphisms [ 177 ] or mutations [ 178 ] of the nesfatin gene, NUCB2, might be associated with the development of obesity. Recently, an increasing number of studies suggest that nesfatin-1 can be a prognostic factor in several types of cancer, like endometrial [ 179 ], gastric [ 180 ], and bladder cancer [ 181 ]. Moreover, NUCB2 may act as a promoter of tumorigenesis and metastasis in breast cancer and renal cell carcinoma [ 182 , 183 ].…”
Section: Nesfatin-1mentioning
confidence: 99%